2013
DOI: 10.1037/a0021996
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder symptoms, depressive symptoms, exercise, and health in college students.

Abstract: Posttraumatic stress disorder (PTSD) symptoms have consistently been associated with poorer health in highly traumatized samples. However, less is known about the relationship between PTSD symptoms, depressive symptoms, and health in nonclinical groups. Because exercise contributes to health, we hypothesized that PTSD symptoms and depressive symptoms would be related to poorer health status, in part, through their association with lower exercise. We examined this in a sample of 200 undergraduates. Health statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
5
30
1
Order By: Relevance
“…Further, students who endorsed cigarette use and alcohol use also reported higher levels of depression and anxiety. These findings are consistent with the above-noted literature, and suggest self-care strategies (i.e., discouraging health compromising behaviors) may hold promise for enhancing the health of high risk, ethnic minority college students (Adams, Moore, & Dye, 2007;Dunn et al, 2005;Fabiano et al, 2009;Hudd et al, 2000;Rutter et al, 2013;Tyson et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Further, students who endorsed cigarette use and alcohol use also reported higher levels of depression and anxiety. These findings are consistent with the above-noted literature, and suggest self-care strategies (i.e., discouraging health compromising behaviors) may hold promise for enhancing the health of high risk, ethnic minority college students (Adams, Moore, & Dye, 2007;Dunn et al, 2005;Fabiano et al, 2009;Hudd et al, 2000;Rutter et al, 2013;Tyson et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…While the existing evidence about the connection between physical health and emotional wellbeing is solid, it is unclear how these studies pertain to ethnic minority college youth, as most included samples that were predominantly Caucasian (Adams et al, 2007;Dunn et al, 2005;Fabiano et al, 2009;Hudd et al, 2000;Rutter et al, 2013;Tyson et al, 2010). As our population becomes more diverse, it can be erroneous to generalize findings from these studies to ethnic minority students, especially given ethnic minority college students have higher rates of depression and anxiety than Caucasian students (Mejia & McCarthy, 2010;Suicide Prevention Resource Center, 2004), and persons of minority race and ethnic backgrounds are more likely to experience poverty and related social stressors (Department of Health and Human Services, n.d., Pincus, Ester, Dewalt, & Callahan, 1998;Williams, 1990).…”
mentioning
confidence: 98%
“…This finding compares with previous studies among university students (Netto et al, 2013;Othieno et al, 2014;Peltzer, 1998;Elhai et al, 2012). Further, the study found, as evidenced in some previous studies (Flores et al, 2010;Karatzias & Chouliara, 2009;Netto et al, 2013;Rutter et al, 2013), that rates o f health risk behaviours were significantly higher among university students who screened positive for PTSD and students with PTSD symptoms were more likely to show multiple health risk behaviours. The study results underscore both the need for preventive services targeting health behaviour-risk reduction in students with PTSD symptoms and the possible benefits o f PTSD treatment for reducing health risk behaviours.…”
Section: Discussionsupporting
confidence: 80%
“…In the case of PTSD, associations with negative health behaviours such as smoking, alcohol use, drug use, condom non-use, and lack of physical activity have been reported (Karatzias & Chouliara, 2009;Netto et al, 2013;Rutter, Weatherill, Krill, & Orazem, 2013). For example, Mexican American adolescents "who experienced height ened posttraumatic stress symptoms reported more alcohol use, more other drug use, involvement in more fights, and more sexual partners."…”
mentioning
confidence: 92%
“…Data generally indicate that individuals with PTSD are less likely to engage in regular physical activity [32] and are more likely to be inactive than those without PTSD [33]. In addition, more severe PTSD symptoms are associated with the lower levels of physical activity [34,35]. Veterans with PTSD are less likely to engage in regular exercise than those with other mental disorders [33].…”
Section: Introductionmentioning
confidence: 99%